2020
DOI: 10.1108/mf-02-2019-0076
|View full text |Cite
|
Sign up to set email alerts
|

Assessing working capital management efficiency of Indian manufacturing exporters

Abstract: PurposeThe purpose of this paper is to empirically investigate the relationship between working capital management (WCM) efficiency and exogenous variables of the Indian manufacturing sector along with its sub-industries that are involved in export activities.Design/methodology/approachPanel regression (fixed effects) was used on a sample of 563 Indian manufacturing firms involved in export activities, covering a time period from 2008 to 2018.FindingsIndustry-wise results showed a significant relation of lever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 31 publications
3
51
0
2
Order By: Relevance
“…Sharma et al (2020) found a positive influence of working capital on firms' performance using data of 150 Bombay Stock Exchange (BSE)-listed firms over the period 2009-2017. Seth et al (2020a) found that a decrease in the CCC (used as a measure for WCM efficiency) is allied with the consequent growth of fixed assets in Indian manufacturing firms over the period 2009-2019. Otherwise, in case of excessive working capital in firms, the unnecessary portion is to be redeployed in higher-valued uses such as fixed assets, causing higher performance in firms (Aktas et al, 2015).…”
Section: Working Capital Management Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Sharma et al (2020) found a positive influence of working capital on firms' performance using data of 150 Bombay Stock Exchange (BSE)-listed firms over the period 2009-2017. Seth et al (2020a) found that a decrease in the CCC (used as a measure for WCM efficiency) is allied with the consequent growth of fixed assets in Indian manufacturing firms over the period 2009-2019. Otherwise, in case of excessive working capital in firms, the unnecessary portion is to be redeployed in higher-valued uses such as fixed assets, causing higher performance in firms (Aktas et al, 2015).…”
Section: Working Capital Management Efficiencymentioning
confidence: 99%
“…Productivity reveals the working capacity of the firm denoting the sales done against wages incurred. Firms need to undergo several nonrecoverable costs for long-term sustainability (Seth et al, 2020a). Such costs comprise creation of distribution channels, customized offerings, advertising, and, most importantly, recognizing the characteristics, inclinations Working capital management efficiency and requirements of every type of customer.…”
Section: Working Capital Management Efficiencymentioning
confidence: 99%
“…WC meets a company entrepreneur's short-term financial needs (Luc, 2018;Tan et al, 2019Tan et al, , 2020. The lower cash flows lead to less need for funding and lower capital costs, which, in turn, increase the levels of investor capital (Seth et al, 2020). Efficient WC has become an essential instrument for continuing companies to improve overall profitability and benefit from the industry (Peng and Zhou, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the situation is important to discover a proper plus advance achievement (result) portion which clearly and straightly describes the influence of the companies' WC productivity (Sawarni et al, 2020). Several investigations identified the CCC's influence on the business' financial achievements (Seth et al, 2020). These investigations addressed an overall return on assets, equity return (ROE), as a proxy for the profits of companies.…”
Section: Introductionmentioning
confidence: 99%